Cell Mechanotransduction With Piconewton Forces Applied by Optical Tweezers - Falleroni, Fabio; Torre, Vincent; Cojoc, Dan (Frontiers in Cellular Neuroscience, 2018)
Mechanical stresses are always present in the cellular environment and mechanotransduction oc-curs in all cells. Although many experimental approaches have been developed to investigate mechanotransduction, the physical properties of the mechanical stimulus have yet to be accurately characterized. Here, we propose a mechanical stimulation method employing an oscillatory optical trap to apply piconewton forces perpendicularly to the cell membrane, for short instants. We show that this stimulation produces membrane indentation and induces cellular calcium transients in mouse neuroblastoma NG108-15 cells, dependent of the stimulus strength and the number of force pulses.